The Commodity of Trade in Contemporary Design. (28th July 2017) - Innella, Giovanni; Anthony Rodgers, Paul
Abstract: The recent growth of festivals, media, and events associated the design industry has had a major impact on the way we conceive, produce, distribute and consume design. This is reflected in the way designers now work, which includes preparing photo-shoots, organizing exhibitions, and creating and disseminating press release materials. Similarly, the network of actors involved has changed, as has the trade of expertise and services they offer. Typically, this includes photographers, commissioning agents, curators, patrons, journalists, and PR personnel amongst others. This research expands the notion of conventional design processes, highlighting the key roles that media and event organizers now play in contemporary design. This research provides significant insights on the nature of a designer's media profile within the contemporary design industry. In so doing, the authors have developed two tools for analyzing contemporary design processes and the trade occurring in commissioned design projects that will be presented in the paper.